Meningkatkan Kompetensi Bahasa Inggris Melalui ‎ Kursus Mingguan (Weekly Course) di Panti Asuhan Puri Kasih ‎Tembilahan Kab. Indragiri Hilir-Riau - Amri, Samsul; Maizarah; Purwanti, Sri Erma; Yeni, Melda (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
Language has a very important role in intellectual, social and emotional development and is a support for success in studying all fields of study. Seeing the importance of this, the English Language Education Study Program, FKIP, Islamic University of Indragiri (UNISI) conducted Community Service (PKM) at the Puri Kasih Orphanage, Tembilahan, Kab. Indragiri Hilir – Riau. This activity is a form of service to the community, especially as a form of implementation of the obligations contained in the Tri Dharma of higher education. The method of implementing this activity is in the form of a course. The purpose of this PKM is to improve English competence through weekly courses. This activity was carried out ± 1 month for four meetings. The PKM participants involved 23 students who resided at the Puri Kasih Tembilahan Orphanage. In this PKM activity, there are several course materials provided, namely: alphabet, self-introduction, greetings, verbs, simple past tense, numbers, personal pronouns, present perfect tense, body parts, possessive pronouns, and descriptive text. The results of this PKM activity show that participants are able to use and apply the material that has been presented. This is supported by the percentage results that 17% of the participants got very good results, 48% of the participants got good results, and 35% got pretty good results. And there are no PKM participants who get less results. This shows that PKM activities that implement weekly English courses are able to make a positive contribution to improving the English competency of PKM participants.